Wie multiplizieren Sie # (3x ^ {2/5} - 3y ^ {1/2}) (6x ^ {2/5} - 4y ^ {1/2}) #?

Antworten:

# 18x ^ (4/5) * - 30x ^ (2/5) 4y ^ (1/2) * 12y #

Erläuterung:

Sie können die FOIL-Methode verwenden.

# (3x ^ (2/5) -3y ^ (1/2)) (6x ^ (2/5) -4y ^ (1/2)) #

F: # 3x ^ (2/5) * 6x ^ (2/5) = 18x ^ (4/5) #

O: # 3x ^ (2/5) * - 4y ^ (1/2) = - 12x ^ (2/5) 4y ^ (1/2) #

ICH: # -3y ^ (1/2) * 6x ^ (2/5) = - 18x ^ (2/5) y ^ (1/2) #

L: # -3y ^ (1/2) * - 4y ^ (1/2) = 12y #

Die Kombination der gleichen Begriffe lautet:

# 18x ^ (4/5) * - 30x ^ (2/5) 4y ^ (1/2) * 12y #